Persistent endotheliopathy in the pathogenesis of long COVID syndrome. (12th September 2021) - Fogarty, Helen; Townsend, Liam; Morrin, Hannah; Ahmad, Azaz; Comerford, Claire; Karampini, Ellie; Englert, Hanna; Byrne, Mary; Bergin, Colm; O'Sullivan, Jamie M.; Martin‐Loeches, Ignacio; Nadarajan, Parthiban; et al.
Abstract: Background: Persistent symptoms including breathlessness, fatigue, and decreased exercise tolerance have been reported in patients after acute SARS‐CoV‐2 infection. The biological mechanisms underlying this "long COVID" syndrome remain unknown. However, autopsy studies have highlighted the key roles played by pulmonary endotheliopathy and microvascular immunothrombosis in acute COVID‐19. Objectives: To assess whether endothelial cell activation may be sustained in convalescent COVID‐19 patients and contribute to long COVID pathogenesis. Patients and Methods: Fifty patients were reviewed at a median of 68 days following SARS‐CoV‐2 infection. In addition to clinical workup, acute phase markers, endothelial cell (EC) activation and NETosis parameters and thrombin generation were assessed. Results: Thrombin generation assays revealed significantly shorter lag times ( p < .0001, 95% CI −2.57 to −1.02 min), increased endogenous thrombin potential ( p = .04, 95% CI 15–416 nM/min), and peak thrombin ( p < .0001, 95% CI 39–93 nM) in convalescent COVID‐19 patients. These prothrombotic changes were independent of ongoing acute phase response or active NETosis. Importantly, EC biomarkers including von Willebrand factor antigen (VWF:Ag), VWF propeptide (VWFpp), and factor VIII were significantly elevated in convalescent COVID‐19 compared with controls ( p = .004, 95% CI 0.09–0.57 IU/ml; p = .009, 95% CI 0.06–0.5 IU/ml; p = .04, 95% CI 0.03–0.44 IU/ml, respectively). In addition, plasma soluble thrombomodulin levels were significantly elevated in convalescent COVID‐19 ( p = .02, 95% CI 0.01–2.7 ng/ml). Sustained endotheliopathy was more frequent in older, comorbid patients, and those requiring hospitalization. Finally, both plasma VWF:Ag and VWFpp levels correlated inversely with 6‐min walk tests. Conclusions: Collectively, our findings demonstrate that sustained endotheliopathy is common in convalescent COVID‐19 and raise the intriguing possibility that this may contribute to long COVID pathogenesis.